(untitled) (Nepalese Journal of Development and Rural Studies, 2022)
This paper aims to synthesize development issues from a Buddhist perspective by taking an analytical universe of ‘well-being’. Methodologically, the paper is a review-based article that follows a systematic review process following different themes of Buddhism, development, and well-being. The major findings of the study include that the development has been contested with the rise of various issues, and its materialistic interpretation has been in crisis both theoretically as well empirically. At this outset, the Buddhist perspective seems to be a more humanistic approach to development which treats underdevelopment as the cause of development. This is the principle of dependent origination, whereby the byproducts of underdevelopment can be analyzed. The Four Noble Truths and the Eightfold Paths are also replicative in the development studies for the socio-economic transformation of society. The material outlet of development doesn’t contribute to the eradication of suffering and miseries from their roots, both in mental and social structure. The paper, therefore, argues that the mainstream approach of development could not sustain development because of the ill-treatment of dukkha and the non-recognition of the sukha. Happiness, pleasure, and non-self are the contributory elements that have been proposed by Buddha’s teachings of Dhamma.